The Relationship between Canadian Nurses and Hospital Management: A Snapshot from 50 Years Ago. Issue 3 (October 2013) - Sibbald, Shannon; Graham, Ross; Sylvester, Shannon
Nurses and management are partners in hospital service delivery. Currently, there are gaps in understanding what fosters this partnership and how it has changed over time. This research investigated the topics that punctuated the nurse-manager relationship from 50 years ago, from the viewpoint of Canadian hospital management. A content review was conducted on the 1962 issues of the "national professional publication for hospital management." Five dominant themes are reported and discussed.